Analisis Efektivitas Bimbingan Kelompok dalam Meningkatkan Empati Kognitif Siswa SDN 02 Kemiling - Sri Murni; Fiki Prayogi; Mareyke Jessy Tanod (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2024)
This study aims to analyze the effectiveness of group guidance services in improving cognitive empathy among students at SDN 2 Kemiling. Cognitive empathy is a student's ability to understand the feelings and conditions of others and to put themselves in their shoes. This study used a descriptive qualitative approach, with data collection techniques including observation, interviews, documentation, and an empathy scale. The results showed that implementing group guidance, consisting of six meetings, increased student activity and participation and improved cognitive empathy scores based on a scale distributed before and after the service. Factors such as cognitive development, mood, and parenting styles also influenced students' empathy levels. These findings indicate that group guidance is an effective strategy for fostering cognitive empathy in elementary school students.